Emerging Infections in Pregnancy: An Updated Review - Subhashis Das; . Nikhil; Gaurav Khichariya; T. Amrutha; Snigdha Sinha (Research Highlights in Disease and Health Research Vol. 7, 2023)
Teratogenicity of numerous infections which develop during pregnancy is well known. Emerging infections are defined as the infections which has increased over the past 10 years or are bound to increase at threatening levels in future. Investigating the effects of emerging infection is vital to ensure that pregnant women are adequately evaluated, suggested and treated but the same is quite difficult and challenging on many aspects. Final impact of emerging infections on fetus is very difficult to ascertain and it is variable as it depends on the etiological factor and gestational time of developing the infection. Some subjects will be asymptomatic clinically or will have nonspecific clinical picture even when the embryo has severe disease making diagnosis more complicated. Current article discusses on evaluation of teratogenicity of emerging infections and how early detection can reduce the severity of infections in pregnancy.